Assessing Optical And Photocatalytic Properties Of Metal Coupled Ti02 Particles - Ishak, Atiikah (Universiti Sains Malaysia, 2018)
Titanium dioxide (TiO2) is famous of its excellent photocatalytic performance in organic pollutants and heavy metal removal. However, deposition of heavy metal (after removal from the solution) on the surface of TiO2 particles might either improve or deteriorate the performance of TiO2 particles in subsequent degradation of organic pollutants. In this project, selected heavy metals were deposited onto the surface of TiO2 particles under both UV and visible light exposure. The removal efficiencies of each metal ions by TiO2 particles were determined. Generally, TiO2 particles were more effective in removal the heavy metals under UV light than visible light irradiation attributed to its wide bandgap. The TiO2 particles removed Cu ions from solution most effectively, followed by Ag, Ni, Cd, Mn and Cr. These metal ions were deposited onto the surface of TiO2 particles, producing metal-coupled TiO2 particles. In the photodegradation of RhB dye study, Cr-, Cu- and Mn-TiO2 particles degraded the RhB dye in faster rate (larger rate constants) than the other metal-coupled TiO2 particles. It was noted that the degradation of RhB dye followed 1st order kinetic reaction regardless the type of metal coupled to TiO2 particles. he reflectivity of metal coupled TiO2 particles was measured. It was found that Ni-TiO2 particles have the highest reflectance but slow photodegradation rate. Limitation to use TiO₂ particles in real application for waste water treatment as waste water is not only contained organic pollutants but also heavy metals ions that could deteriorate the performance of TiO₂ particles.